Haiti - Blashfield, Jean F. (New York : Children's Press, 2008)
Introduces children to the people, culture, geography, history, and animals of Haiti, with color photographs, original maps, interactive sidebars, fast-facts, and Internet resources to help children learn more about the country.
Spirit and strength -- The shape of land and sea -- Threatened beauty -- A turbulent history -- The changeable government -- Manufacturing hope -- The people of Haiti -- Spiritual life -- Sights and sounds -- Daily life.
Includes bibliographical references (p. 134) and index.
8.8
5-8
Keywords: Haiti -- Juvenile literature; Haiti; Haiti